Analisis Teknik Relaksasi dan Mobilisasi untuk Mengatasi Nyeri pada Ibu Post Sectio Caesarea - Rahmadyanti, Rahmadyanti; Nani, Nani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of the Benson relaxation technique on the pain scale in post-SC surgery patients at RSU Proklik Karawang in 2023. The research method used pre-experiment with a research design of one group pre and post test design. The results of the research showed that there was a decrease in the average pain score before and after Benson relaxation by 6.13 on the pain scale and the results of the t-test showed that there was a significant difference in pain scores before and after Benson relaxation intervention in patients after caesarean section Sig. (2-tailed) of 0.000 <0.005. In conclusion, there is an effect of Benson relaxation on reducing pain in post-SC surgery patients at RSU Proklik and it is hoped that Benson relaxation can be used as a reference for alternative treatment to reduce pain in post-SC surgery patients. Keywords: Mobilization, Post-operative SC, Pain Scale, Benson Relaxation Technique